Rural regions as key locations for the circular bioeconomy: insights from the northern interior of Portugal - Brandão, Ana Sofia (2022)
Rural areas have often been singled out as strategic locations for the implementation of the Circular Bioeconomy (CBE) concept. This study aims to carry out a detailed analysis of the northern interior of Portugal, focusing on its business dynamics within the CBE. Two representative case studies were selected and critically compared with successful cases from European Nordic countries. The results showed that, generally, waste is managed inefficiently and with little benefit. The cross-comparison with the Nordic CBE model revealed that there is a lack of synergies and collaboration between different stakeholders, from the most basic to the most advanced level. Also, investment in more applied education, as well as a culture based on trust and dialogue, would greatly contribute to the successful implementation of regional CBE policies. In short, innovation, not only in products and services, but mainly in partnerships is key to a sustainable economic growth in rural regions.